Bandgap engineering of Na1-xAgxSbS2 alloys for photovoltaic applications. (August 2022) - Sa, Rongjian; Zhang, Qiqi; Yang, Yuqing; Liu, Diwen
Highlights: The electronic and optical properties of the alloyed Na1- x Ag x SbS2 compounds are studied. The stability and band gap of NaSbS2 can be tuned by doping Ag. Na0.50 Ag0.50 SbS2 shows great potential for photovoltaic applications. Abstract: NaSbS2 has shown the potential to be a light absorber material for solar cells in recent years. The efficiency of NaSbS2 can be improved by reducing the band gap to the desired value. In this paper, a theoretical approach is used to explore the electronic and optical properties of the alloyed Na1- x Ag x SbS2 compounds. The results show that NaSbS2 has good stability when the concentration of Ag doping is 50%. The monoclinic structure is not thermodynamically stable for AgSbS2 . The PBE0 functional is used to reveal the electronic structures of the studied compounds. The indirect band gap nature remains unchanged for each compound. An optimum band gap value (∼1.4 eV) can be realized for Na0.50 Ag0.50 SbS2, and the light absorption intensity and width are increased. The results indicate that Na0.50 Ag0.50 SbS2 shows great potential for photovoltaic applications. Therefore, alloying is proposed to be an effective way to improve the photovoltaic efficiency of NaSbS2 . Graphical abstract: Image, graphical abstract